Explosions managing the aftermath : delegate information : 12 July 1993. (Institution of Civil Engineers, 1993)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held on 12 July 1993.